PENGARUH VARIASI DOSIS BIOPESTISIDA BATANG SERAI (Andropogon nardus L.) TERHADAP PERTUMBUHAN DAN KETAHANAN SERANGAN HAMA BAYAM MERAH (Alternanthera amoena Voss) - Rahayu, Wiwit Turindah; -, Achyani; widowati, Hening (BIOLOVA, 2020)
Abstract: The purpose of this study was to determine the effect of variations in the dosage of lemongrass biopesticides and the best dose on the growth and resistance of red spinach pests. This research is also expected to be a potential source of learning biology. The research design used was a Completely Randomized Design (CRD) with one control and 3 treatments, P1: citronella stem biopesticide dose 35% P2: citronella stem biopesticide dose 40%, and P3: citronella stem biopesticide dose 45%, with each treatment using 6 replications. Growth and resistance of red spinach pests were analyzed using 1-way ANAVA. The results showed there was an effect of variations in the dosage of lemongrass biopesticide on growth and resistance of red spinach pests because the Fcount value was greater than the Ftable in the Chi-square table. 45% dosage of lemongrass biopesticide has the best influence on the growth and resistance of red spinach pests. This research also has the potential as a source of learning biology by using a scientific approach